2016
DOI: 10.1007/978-3-319-39583-8_44
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Extraction of Prerequisites Among Learning Objects Using Wikipedia-Based Content Analysis

Abstract: Identifying the prerequisite relationships among learning objects is a crucial step for faculty and instructional designers when they try to adapt them for delivery in their general education distance courses. We propose a generalpurpose content-based approach for facilitating this step by means of semantic analysis techniques: the learning objects are associated to WikiPedia pages (topics), and their dependency is obtained using the classification of those topics supported by Wikipedia Miner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Of particular relevance here is the line of related work, where researchers have investigated how machine learning and large-scale, open-access resources such as Wikipedia can be utilized to generate various types of educational content and interactions with the aim of scaling up computer-based learning systems and addressing the needs of their students (Brunskill et al, 2018;Dinan et al, 2018;Guo et al, 2016;Willis et al, 2019). In particular, it has been shown that the use of NLP techniques in application to Wikipedia may be helpful in generating pedagogically motivated concept maps to be used within an ITS (Lahti, 2009); identifying pre-requisite relations and sequencing among learning concepts to better model the learning path of the student and assess gaps in student's understanding of the subject (De Medio et al, 2016;Ramírez-Noriega et al, 2018;Talukdar & Cohen, 2012); and generating a variety of pedagogical interventions ranging from open questions Shah et al, 2017) to multiple-choice quizzes (Guo et al, 2016;Tamura et al, 2015) across a number of subject domains.…”
Section: Intelligent Tutoring Systemsmentioning
confidence: 99%
“…Of particular relevance here is the line of related work, where researchers have investigated how machine learning and large-scale, open-access resources such as Wikipedia can be utilized to generate various types of educational content and interactions with the aim of scaling up computer-based learning systems and addressing the needs of their students (Brunskill et al, 2018;Dinan et al, 2018;Guo et al, 2016;Willis et al, 2019). In particular, it has been shown that the use of NLP techniques in application to Wikipedia may be helpful in generating pedagogically motivated concept maps to be used within an ITS (Lahti, 2009); identifying pre-requisite relations and sequencing among learning concepts to better model the learning path of the student and assess gaps in student's understanding of the subject (De Medio et al, 2016;Ramírez-Noriega et al, 2018;Talukdar & Cohen, 2012); and generating a variety of pedagogical interventions ranging from open questions Shah et al, 2017) to multiple-choice quizzes (Guo et al, 2016;Tamura et al, 2015) across a number of subject domains.…”
Section: Intelligent Tutoring Systemsmentioning
confidence: 99%
“…The identification of prerequisite relationships among Learning Objects has been addressed in [49], [50]. Learning Objects are associated to Wikipedia pages (topics), and their dependency is obtained using the classification of those topics supported by Wikipedia Miner [51].…”
Section: B Elicitation Of Relationships For Educational Purposesmentioning
confidence: 99%
“…Secondly, we annotated each set of transcripts, pertaining the same concept, by means of the Wikipedia Miner Toolkit. As a result we obtained, for each set of transcripts, a set of Wikipedia web pages, pertaining the same concept [3,9,11,8,10]. Then, we trained three binary learners: a decision tree, a naive-bayes and a multi-layer perceptron to inference whether a didactic relationship between the two LUs, both given in input, does exist or not.…”
Section: Motivations Goals and Related Workmentioning
confidence: 99%